2015
DOI: 10.1167/15.6.5
|View full text |Cite
|
Sign up to set email alerts
|

Crowding, grouping, and object recognition: A matter of appearance

Abstract: In crowding, the perception of a target strongly deteriorates when neighboring elements are presented. Crowding is usually assumed to have the following characteristics. (a) Crowding is determined only by nearby elements within a restricted region around the target (Bouma's law). (b) Increasing the number of flankers can only deteriorate performance. (c) Target-flanker interference is feature-specific. These characteristics are usually explained by pooling models, which are well in the spirit of classic models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
142
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 119 publications
(149 citation statements)
references
References 121 publications
7
142
0
Order By: Relevance
“…Our results suggest that crowding occurs in a slow, recurrent process. Using EEG source localization techniques, we found that high-level visual areas reflected crowding better than V1 supporting, again, the idea that crowding is linked to grouping and appearance (Herzog et al, 2015).…”
Section: Introductionsupporting
confidence: 61%
See 3 more Smart Citations
“…Our results suggest that crowding occurs in a slow, recurrent process. Using EEG source localization techniques, we found that high-level visual areas reflected crowding better than V1 supporting, again, the idea that crowding is linked to grouping and appearance (Herzog et al, 2015).…”
Section: Introductionsupporting
confidence: 61%
“…Crowding depends on multiple grouping cues, including similarity and pattern completion as was shown in previous studies (Herzog et al, 2015;Manassi et al, 2012;Sayim et al, 2008). For example, a red vernier was flanked by red or green flankers.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…When a peripherally presented target, which is easily recognized on its own, is surrounded by nearby flankers, its recognition performance is often largely disrupted (Levi, ; Whitney & Levi, ). This phenomenon, referred to as crowding, is not only a well‐established effect in spatial vision which occurs under a wide range of conditions and tasks but also a basic property of peripheral vision that sets the limit for peripheral perception (Anderson, Dakin, Schwarzkopf, Rees, & Greenwood, ; Chen et al., ; Chicherov & Herzog, ; Chicherov, Plomp, & Herzog, ; Greenwood, Sayim, & Cavanagh, ; Herzog, Sayim, Chicherov, & Manassi, ; Levi, ; Manassi, Sayim, & Herzog, ; Ronconi, Bertoni, & Marotti, ; Shin, Chung, & Tjan, ; Whitney & Levi, ; Xiong, Yu, & Zhang, ; Zhang, Zhang, Liu, & Yu, ). It is of vital importance to study crowding and its underlying neural mechanism, as it would advance our understandings of conscious vision and object recognition.…”
Section: Introductionmentioning
confidence: 99%